The attributes of informal science education: A science communication perspective - Stocklmayer, S.; Rennie, Leonie (2017)
© Springer International Publishing AG 2017. Informal science education is, increasingly, focusing on the role of science in the adult world beyond school, for which lifelong learning about aspects of science is the educational goal. Science communication is concerned with the public awareness of science, which intersects with this goal in many ways. Given that they are both focused on enhancing public interest in and awareness about science, closer ties between them can strengthen the benefits of each. Like informal science education, the discipline of science communication draws its theoretical framework from a variety of other disciplines, including formal education and cognate fields. It is, however, more wide-ranging, because science communicators take up careers which include positions in science institutions, government, the media, and informal science education. In this chapter we first identify the attributes of informal science education that underpin science learning in informal contexts, both for school-age students and the wider public, and continue with an overview of the field of science communication. We discuss the kinds of skills and knowledge that are intrinsic to effective science communication, drawing upon research into the public communication of science and the various models of science communication that pertain to this wider aim. Finally we propose a framework that amalgamates the attributes with those skills and knowledge with a particular focus on those which are valuable to those communicating science informal contexts. The context of informal learning has a very broad application in science communication, from the notion of a more passive audience through to a fully participatory experience. Those who provide the experience, whether it be at a zoo, a museum, or via a television program, need to be doing so from an informed, professional perspective which incorporates and exploits science communication skills.